Coordinated Optimization Model of Planning and Operation of Integrated Energy System Based on Mixed Integer Programming. Issue 1 (December 2020) - Wang, Xiaohui; Xu, Nan; Liu, Yaqiong; Lu, Yanchao
Abstract: In recent years, the planning and operation of integrated energy system has received extensive attention. The traditional two-stage nonlinear model of planning and operation has problems such as inability to reach the global optimum and low solution efficiency. By linearizing the nonlinear constraints, this paper introduces a coordinated optimization model of planning and operation of integrated energy system based on mixed integer programming, which takes the minimum annual cost as the objective function and considers the coupling characteristics of electrical, thermal, and cooling load. The model achieves the optimal capacity configuration and operating scheme at the same time. Results of the testing data verify the effectiveness of the model.